Tradisi Kuliner dan Identitas Budaya: Sebuah Kajian Genealogis Festival Grebeg Gethuk di Jawa, Indonesia : Culinary Tradition and Cultural Identity: A Genealogical Study of Grebeg Gethuk in Java, Indonesia - Theresia Pinaka Ratna Ning Hapsari; Hubbi Saufan Hilmi (Universitas Tidar, 2026)
This study explores the cultural significance of Grebeg Gethuk a traditional culinary festival in Magelang, Java, Indonesia, through a genealogical lens. Grebeg Gethuk festival rooted in Java's rich culinary heritage, has evolved over time while maintaining its traditional values. By tracing its historical and cultural origins, this research reveals how the festival has adapted to the challenges of modernization and globalization. Using a qualitative approach, data was collected through in-depth interviews, participant observation, and document analysis. The findings highlight the role of Grebeg Gethuk festival in preserving local cultural identity, fostering social solidarity, and promoting traditional cuisine as a marker of community heritage. The research also addresses the impact of globalization on local traditions and how Grebeg Gethuk festival functions as a mechanism for cultural preservation and economic sustainability through tourism. This research contributes to broader discussions on cultural identity, culinary traditions, and resilience of local practices in the face of global change.